Hydrostatic pressure effect on the magnetocaloric behavior of Ga-doped MnNiGe magnetic equiatomic alloy. (23rd February 2016) - Dutta, P; Das, D; Chatterjee, S; Pramanick, S; Majumdar, S
Abstract: The magnetocaloric properties of a new class of ferromagnetic shape memory alloys of nominal composition MnNiGe0.928 Ga0.072 have been investigated in ambient conditions as well as in the presence of external hydrostatic pressure. Both inverse (6.35 Jkg −1 K −1 for 0 − 50 kOe around 160 K) and conventional (−4.54 Jkg −1 K −1 for 0–50 kOe around 210 K) magnetocaloric effects (MCEs) have been observed around the structural and magnetic transitions respectively. The sample can be thought of as being derived from the parent MnNiGe alloy, where Ga was doped at the expense of the Ge atom. Ga doping at Ge sites brings down the martensitic transition temperature to below room temperature and induces ferromagnetism by affecting the lattice volume of the alloy. However, below the first-order martensitic transition the alloy loses its ferromagnetism. Application of external hydrostatic pressure results in a revival of ferromagnetic interactions in the martensitic phase of the alloy and a considerable increase in the refrigeration capacity around the conventional MCE region.